Некоторые вопросы экономичности и надежности электрохозяйства энергоемких предприятий - Назарок, В. И.; Антонов, В. Г. (НТУ "ХПИ", 2010)
In this article have been examine the question of reliability of improvement of high-voltage power network at the expense of high harmonic components attenuation due to phase compensating equipment (AREVA – NOKIAN CAPACYTORS) on demand side.
Some questions of efficiency and dependability of electric equipment of power-intensive industries
Keywords: печь электросталеплавильная; печь дуговая; установка печь-ковш; нагрузка; трансформатор; показатель качества электроэнергии; устройство фильтрокомпенсирующее; реактор тиристорно-управляемый